Investigation of Nutrients Controlling Bacterial Regrowth in a PEX and Stainless Steel Plumbing Water System - Nam, Sangchul; Lee, Yoon-Jin (Asian Journal of Chemistry, 2010)
The growth of suspended microorganisms and biofilm development, as measured by heterotrophic plate count bacteria in PEX and stainless steel pipes, which are often used in the hot water system in Korea are investigated. There was no significant difference in the level of attached microorganisms from variations in water temperature on PEX and stainless steel pipes. However, the numbers of suspended microorganisms were higher at 55 ºC compared to 20 ºC in effluents from the PEX pipe. In order to understand the contribution of organic and inorganic nutrients to biofilm development, bacteria grown in tap water without supplements on PEX and stainless steel pipes was compared to bacteria grown with added acetate, phosphate or mixed inorganics and acetate. Bacterial multiplication in the PEX pipe was appreciably higher when the mixed inorganic cocktail and acetate were added. The density of attached microbes increased with the addition of phosphorus for both pipes. The influence of nutrients was comparatively higher in the PEX pipe with hot tap water. The application of chlorine was not found to be effective for controlling bacterial growth in high temperature tap water in PEX pipe and the level of UV-254 and dissolved organic carbon in the effluent increased after hot water stagnation.